2021
DOI: 10.1210/endocr/bqab117
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms Within the Female HPG Axis: From Physiology to Etiology

Abstract: Declining female fertility has become a global health concern. It results partially from an abnormal circadian clock caused by unhealthy diet and sleep habits in modern life. The circadian clock system is a hierarchical network consisting of central and peripheral clocks. It not only controls the sleep-wake and feeding-fasting cycles but also coordinates and maintains the required reproductive activities in the body. Physiologically, the reproductive processes are governed by the hypothalamic-pituitary-gonadal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 122 publications
0
28
0
Order By: Relevance
“…Proper SCN rhythmicity, mediated by Clock genes, stimulates Gonadotropin Releasing Hormone (GnRH) pulsatility and pituitary luteinizing hormone (LH) release through two different neural networks: vasoactive intestinal peptide (VIP)-containing neurons and arginine vasopressin (AVP)-containing neurons [ 18 ]. VIP-containing neurons project from the SCN to GnRH neurons directly, whereas AVP-containing neurons project from the SCN to anteroventral periventricular nucleus Kisspeptin neurons and stimulate GnRH and LH secretion indirectly [ 22 24 ]. Clock mutant mice exhibit decreased expression of AVP in their SCN and have irregular estrous cycles without an LH surge [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Proper SCN rhythmicity, mediated by Clock genes, stimulates Gonadotropin Releasing Hormone (GnRH) pulsatility and pituitary luteinizing hormone (LH) release through two different neural networks: vasoactive intestinal peptide (VIP)-containing neurons and arginine vasopressin (AVP)-containing neurons [ 18 ]. VIP-containing neurons project from the SCN to GnRH neurons directly, whereas AVP-containing neurons project from the SCN to anteroventral periventricular nucleus Kisspeptin neurons and stimulate GnRH and LH secretion indirectly [ 22 24 ]. Clock mutant mice exhibit decreased expression of AVP in their SCN and have irregular estrous cycles without an LH surge [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Female mice lacking Bmal1 also do not exhibit any LH or follicle stimulating hormone (FSH) surge [ 29 ]. Within granulosa cells, periodic fluctuations in estradiol and progesterone have been observed and are mediated via circadian regulation of aromatase [ 24 ]. The Bmal1 - Clock dimer binds to the E-box sites of Cyp19a1 and StAR promoter, regulating their transcription and the synthesis of estrogen and progesterone [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This axis produces gonadotropins, mainly FSH and LH [ 25 ], and plays important physiological roles. Recent studies have shown that the HPG axis regulates the reproductive process in a time-dependent manner, and circadian rhythm disorders can lead to diseases, such as polycystic ovarian syndrome (PCOS) and premature ovarian insufficiency (POI) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%